PROSPECTS FOR THE DEVELOPMENT OF THE POLITICAL AND PROFESSIONAL CULTURE OF THE EMPLOYEES OF THE INTERNAL AFFAIRS SERVICE (Conferencea, 2023)
The political culture of the employees of the internal affairs bodies should be adapted to the changes in social life and should serve the active participation of the youth in civil relations. In Uzbekistan, in accordance with international standards and ratings, the activity of the police service at the level of the police service requires the implementation of conscientiously popular military service in the demonstration of professional and moral-ethical culture and attitude. In this case, it was studied that the formation of political knowledge and skills of an employee depends on many tools (media, various trainings, professional development, etc.), and their criteria and mechanisms (internal structures) were detailed. Theoretical and practical conclusions, proposals and recommendations aimed at future objective and subjective problems of further improvement of political culture of industry workers and their solutions were presented.